2018
DOI: 10.1016/j.jid.2017.05.038
|View full text |Cite
|
Sign up to set email alerts
|

MSX1-Induced Neural Crest-Like Reprogramming Promotes Melanoma Progression

Abstract: Melanoma cells share many biological properties with neural crest stem cells. Here we show that the homeodomain transcription factor MSX1, which is significantly correlated with melanoma disease progression, reprograms melanocytes and melanoma cells toward a neural crest precursor-like state. MSX1-reprogrammed normal human melanocytes express the neural crest marker p75 and become multipotent. MSX1 induces a phenotypic switch in melanoma, which is characterized by an oncogenic transition from an E-cadherin—hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 36 publications
(42 reference statements)
0
39
0
2
Order By: Relevance
“…Deregulation of FOXD1 expression during tumorigenesis has also been described in non‐small cell lung cancer (NSCLC), prostate cancer and glioma . In the context of melanoma transformation, although the upregulation of TWIST1 and MSX1 is strongly correlated with disease progression, no information is currently available on the role of FOXD1 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deregulation of FOXD1 expression during tumorigenesis has also been described in non‐small cell lung cancer (NSCLC), prostate cancer and glioma . In the context of melanoma transformation, although the upregulation of TWIST1 and MSX1 is strongly correlated with disease progression, no information is currently available on the role of FOXD1 …”
Section: Discussionmentioning
confidence: 99%
“…High SLUG expression is seen during early melanomagenesis, however high TWIST1 expression is present in invasive melanoma cells . BRN3A is required for melanoma survival, and forced MSX1 expression in melanocytes leads to a multipotent state and tumor progression …”
Section: Introductionmentioning
confidence: 99%
“…Additional evidence for a ZEB1 role in melanoma CSC maintenance comes from another study in which the neural crest cell marker Msh homeobox 1 (MSX1) was shown to reprogram differentiated melanocytes to more invasive, NCSC-like melanocytes that can differentiate into other NCSC derivatives, such as neuronal cells. This cell state reprogramming coincides with an increase in ZEB1 and a decrease in ZEB2 and MITF expression [ 112 ]. Moreover, that study has shown that reactivation of notch receptor 1 (NOTCH1) signalling fully reprogrammed differentiated melanocytes into multipotent NCSC-like cells.…”
Section: Zeb1 and Zeb2 In Melanoma Phenotype Switchingmentioning
confidence: 99%
“…In other cancers, similar tumor cell-intrinsic mechanisms determine liver metastasis. In melanoma, for example, MSX1induced neural crest-like reprogramming promotes hepatic metastasis (5).…”
Section: Introductionmentioning
confidence: 99%